Disentangling cognitive inflexibility in major depressive disorder: A transcranial direct current stimulation study. Issue 7 (14th May 2022) - Koshikawa, Yosuke; Nishida, Keiichiro; Yamane, Tomonari; Yoshimura, Masafumi; Onohara, Ai; Ueda, Satsuki; Ishii, Ryouhei; Kinoshita, Toshihiko; Morishima, Yosuke
Abstract : Background: Cognitive dysfunction is a persistent residual symptom in major depressive disorders (MDDs) that hinders social and occupational recovery. Cognitive inflexibility is a typical cognitive dysfunction in MDD and refers to difficulty in switching tasks, which requires two subcomponents: forgetting an old task and adapting to a new one. Here, we aimed to disentangle the subcomponents of cognitive inflexibility in MDD and investigate whether they can be improved by transcranial direct current stimulation (tDCS) on the prefrontal cortex. Methods: The current study included 20 patients with MDD (seven females) and 22 age‐matched healthy controls (HCs) (seven females). The participants received anodal tDCS on either the dorsomedial prefrontal cortex (DMPFC) or dorsolateral prefrontal cortex (DLPFC) in a crossover design. Before and after the application of tDCS, the participants performed a modified Wisconsin Card Sorting Test, in which the task‐switching rules were explicitly described and proactive interference from a previous task rule was occasionally released. Results: We found that the behavioral cost of a task switch was increased in patients with MDD, but that of proactive interference was comparable between patients with MDD and HCs. The response time for anodal DMPFC tDCS was decreased compared with that for anodal tDCS on the DLPFC in MDD. Conclusions: These findings suggest that cognitive inflexibility in MDD is primarily explained by the difficulty to adapt to a new task and environment, and that tDCS on the DMPFC improves behavioral performance during cognitively demanding tasks that require conflict resolution.